Threat by Association, Islamic Puritanism and Conspiracy Beliefs Explain A Religious Majority Group's Collective Protest Against Religious Minority Groups. (March 2023) - Mashuri, Ali; Osteen, Chad
This article addresses the question of why members of a majority group, despite their more powerful status, may protest against low-power minority groups. The present study addressed this question in the context of immanent intergroup relations between Muslims, as the majority group, and non-Muslims, as the minority group, in Indonesia. It is argued that at the core of such collective protests is a threat by association, a perception of the majority group members that the minority groups are in league with the West which threatens the existence of Muslims worldwide. Based on data collected using a survey questionnaire from Indonesian Muslims ( N = 418) this study tested a hypothesised model using threat by association posed by the minority groups, Islamic puritanism and beliefs relating to western conspiracy to predict collective protests and intolerant intentions against non-Muslim minorities in Indonesia by using MPlus version 7.0. The hypothesised model found empirical support. The relationship between threat by association and Islamic puritanism with collective protests was mediated by Western conspiracy beliefs. It was also found that support for collective protests got translated into majority group members' religious intolerant intentions against the people belonging to the non-Muslim minority groups. The article discusses the theoretical implications and research limitations of these empirical findings.